La estabilidad emocional en el Nivel Inicial. - Aquieta Masapanta, Lourdes Angélica (2018)
The present research on emotional stability at initially developed was made with the objective to determine the factors that affect emotional well-being through interaction with the people surrounding the children in order to favor teaching-learning by establishing emotional bonds, knowing the problematic of scarce educational focus to strengthen this dimension on infantile development at initial education. The research methodology that has been applied includes a qualitative and a quantitative approach; specifically, bibliographic-documentary research and field research, among with the non-experimental and logical inductive method to reach the exploratory level. The techniques used were surveys to student's parents and interviews to teachers of the initial education level. The contribution of the research was a theorical and a formative contribution for the professional preparation of the researchers, because it showed that is necessary to recognize the importance that emotional development at initial education has to education guarantee quality. At the conclusion of the investigation it has been determined that the emotional stability is a characteristic of the personality, determined by the ability of the child to manage their emotions and use them positively for their development; thetefore, it should be stimulated at the initial education levels because on first years of life, the boy and the girl learn to control their emotions and establish emotional bonds. 57% of children from Joaquin Lalama Elementary school show impulsive attitudes that reflect poor control over their emotions; in the classroom they are easily distracted, doing other tasks and they have others behavioral problems that affect their emotions; and learnig process. Therefore, it is necessary in the classroom of initial education, work with children over their emotional stability with activities such as games, story telling, among others. That will allow the child to know and master the different emotions.